Efeito do gluconato de cálcio em blendas poliméricas sericina / álcool poli (vinílico) - Gamero, Patricia Dias (2017)
The research and development of new technologies in the field of chemical materials and processes has been the subject of many scientific works that seek innovations. The use of polymer materials for application in the biomedical area is constantly increasing, and they have important applications as controlled system of drug release, cell encapsulation, regeneration of muscle tissues and blends for topical use. The polymers may be synthetic such as poly (vinyl alcohol) (PVA) and natural also called biopolymers such as sericin (SER) formed by Bombyx mori. For the use of biopolymers it is extremely important to evaluate some characteristics such as plasticizers and / or crosslinking agents in order to produce blends with better properties to the intended purpose. The objective of this study was to evaluate the effect of calcium gluconate (GLU) on SER / PVA polymer blends aiming at a possible application in materials with controlled release of drugs, to prepare SER / PVA polymer blends with glycerol (GLI) And calcium gluconate and compositions and characterize systems such films for moisture content, infrared spectroscopy in Fourier transform attenuated total reflectance module, thermogravimetric analysis, scanning electron microscopy, tensile tests and monitor calcium content in solution Resulting from the release of the calcium gluconate present in the SER / PVA blends films by atomic absorption spectroscopy. It was observed higher thermal stability in GLU films as an additive due to its possible crosslinking effect related to the Ca2+ ions present in the blends, with a higher moisture content when GLY is used. In the FTIR-ATR studies it can be observed that GLU causes Alteration of the spectroscopic profile of the film between 50% and 60% of the SER content differently than occurs with GLY (40% - 50%) In the morphology studies a phase separation was observed in both GLY and GLU films, In the traction results the GLY presented the expected plasticity since the GLU eliminates the plasticity of the SER / PVA film but significantly increases the resistance of the material, a clear consequence of more intense interactions inside the material. It also showed a positive release profile that can be modulated in SER / PVA compositions, these results demonstrating the viability of the film as a release material. Thus, GLU has a multiple function in the proposed polymer blend as well as acting as a crosslinker can also act as a drug.